A Retrospection of Chaotic Phenomena in Electrical Systems. (1998) - Kumar, Umesh
Abstract : In the last decade new phenomena have been observed in all areas of non linear dynamics, principal among these being 'Chaotic phenomena'. Chaos has been reported virtually from every scientific discipline. This paper summarizes a study of the chaotic phenomena in electrical systems and attempts to translate the mathematical ideas and techniques into language that engineers and applied scientists can use to study 'Chaos'. Towards this end, the paper has summarized the study of chaos in several examples like Chua's circuit family; Folded Torus circuit; non-autonomous circuits; switched capacitor circuits and hyper-chaos circuits. As observed in power systems, control systems and digital filters, chaos has been exhibited and shown on examples.